Impaired growth in rural Gambian infants exposed to aflatoxin: a prospective cohort study - Sinead Watson; Sophie E. Moore; Momodou K. Darboe; Gaoyun Chen; Yu-Kang Tu; Yi-Ting Huang; Kamilla G. Eriksen; Robin M. Bernstein; Andrew M. Prentice; Christopher P. Wild; Ya Xu; Michael N. Routledge; et al. (BMC, 2018)
Abstract Background Exposure to aflatoxin, a mycotoxin produced by fungi that commonly contaminates cereal crops across sub-Saharan Africa, has been associated with impaired child growth. We investigated the impact of aflatoxin exposure on the growth of Gambian infants from birth to two years of age, and the impact on insulin-like growth factor (IGF)-axis proteins. Methods A subsample (N = 374) of infants from the Early Nutrition and Immune Development (ENID) trial (ISRCTN49285450) were included in this study. Aflatoxin-albumin adducts (AF-alb) were measured in blood collected from infants at 6, 12 and 18 months of age. IGF-1 and IGFBP-3 were measured in blood collected at 12 and 18 months. Anthropometric measurements taken at 6, 12, 18 and 24 months of age were converted to z-scores against the WHO reference. The relationship between aflatoxin exposure and growth was analysed using multi-level modelling. Results Inverse relationships were observed between lnAF-alb and length-for-age (LAZ), weight-for-age (WAZ), and weight-for-length (WLZ) z-scores from 6 to 18 months of age (β = − 0·04, P = 0·015; β = − 0·05, P = 0.003; β = − 0·06, P = 0·007; respectively). There was an inverse relationship between lnAF-alb at 6 months and change in WLZ between 6 and 12 months (β = − 0·01; P = 0·013). LnAF-alb at 12 months was associated with changes in LAZ and infant length between 12 and 18 months of age (β = − 0·01, P = 0·003; β = − 0·003, P = 0·02; respectively). LnAF-alb at 6 months was associated with IGFBP-3 at 12 months (r = − 0·12; P = 0·043). Conclusions This study found a small but significant effect of aflatoxin exposure on the growth of Gambian infants. This relationship is not apparently explained by aflatoxin induced changes in the IGF-axis.